The results of the annual RAACS Conceptual Competition - Bush, Dmitry (project baikal, 2026)
The article highlights the results of the RAACS Competition 2026, the theme of which is “Residential Building of the 22nd Century”. The article gives an analysis of the works presented by architects from many Russian regions. Along with the advantages, the disadvantages of most projects are also noted, including the lack of memorable architectural ideas and manual graphics skills. It is concluded that it is important to promote this type of creativity, which is necessary to obtain results comparable to the masterpieces of the masters of “paper architecture”.